2021
DOI: 10.46606/eajess2021v02i02.0084
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Perception on the Challenges of Continuous Assessment Implementation between 2017 and 2018

Abstract: Continuous assessment is an integral part of the instruction as it determines whether the goals of education are being met during or at the end of the instructional period. The updated curriculum (2015-2022) in the Zimbabwean Primary and Secondary Schools introduced the continuous assessment which was abandoned a few months after its inception. This study sought to evaluate from the teachers’ perspective the challenges which led to premature abandoning of the continuous assessment aspect. Qualitative approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…The findings reveal that the existing socio-economic factors are worsening the situation. While CALA seems to be an effective pedagogical and assessment tool, parents, teachers and learners face challenges which shape their perceptions on CALA (Sithole et al, 2021). Parents express discontentment that they have never been told about the importance of CALA and most of them do not even know what it is all about (Pulitzer Center, 10 March 2023, Sithole et al, 2021).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…The findings reveal that the existing socio-economic factors are worsening the situation. While CALA seems to be an effective pedagogical and assessment tool, parents, teachers and learners face challenges which shape their perceptions on CALA (Sithole et al, 2021). Parents express discontentment that they have never been told about the importance of CALA and most of them do not even know what it is all about (Pulitzer Center, 10 March 2023, Sithole et al, 2021).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…While CALA seems to be an effective pedagogical and assessment tool, parents, teachers and learners face challenges which shape their perceptions on CALA (Sithole et al, 2021). Parents express discontentment that they have never been told about the importance of CALA and most of them do not even know what it is all about (Pulitzer Center, 10 March 2023, Sithole et al, 2021). Parents want their children to pass examinations and if the curriculum model is failing to meet their expectation, they are likely to dump it.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research by Sithole et al (2021) on teacher perception of the implementation of continuous assessment in Zimbabwean schools revealed that teachers have a negative attitude towards continuous assessment. This attitude emanated from poor preparation before the introduction of the curriculum reform.…”
Section: Teacher Attitude Towards Continuous Assessmentmentioning
confidence: 99%